Fracture analysis of defect Chlorinated Poly Vinyl Chloride pipes based on burst pressure and prediction their fraction of life (Fracture and Structural Integrity, 2023)
Most Chlorinated Poly Vinyl Chloride (CPVC) resins contain 63-69 % chlorine, in particular those used for the extrusion of plumbing tubes, due to this chlorination of basic PVC, CPVC offers a mixture of corrosion resistance and low installation costs for its main applications requiring service in non-ambient conditions. CPVC replaces copper owing to its economic gain and by virtue of its pressure resistance characteristics. In this article, we have been interested in fracture analysis and damage modeling of CPVC tubes by subject CPVC samples to burst pressure tests. We performed a set of burst tests on virgin and artificially damaged CPVC pipe at different notch lengths, then submitted the specimens to burst pressure tests, in addition to recording the pressure and time during these tests for use in conducting the study. The results of the burst tests were exploited to estimate the damage and reliability of the material, these two parameters allow us to follow the degradation of the pipes used; subsequently, we determined a new relationship between these two parameters through the fraction life. This makes it possible to predict the moment of damage acceleration and to intervene at the right time for engaging predictive maintenance.
Keywords: burst tests; pressure; CPVC pipes; fracture; damage; reliability